From canonical to unique: extension of a lipophilicity scale of amino acids to non-standard residues - Antonio Viayna; Paulina Matamoros; David Blázquez-Ruano; William J. Zamora (Exploration of Drug Science)
Aim: The lipophilicity of amino acids plays a crucial role in delineating their physicochemical properties, offering insights into solubility, binding affinity, and bioavailability, properties that are a cornerstone for the use of peptides as therapeutic agents. In this study, we employ the integral equation formalism polarizable continuum model/Miertus-Scrocco-Tomasi (IEFPCM/MST) implicit solvation model to compute the n-octanol/water partition coefficient, serving as a lipophilic descriptor for non-standard amino acids. This approach allows us to expand upon our prior scale developed for canonical amino acids. Methods: Using the IEFPCM/MST implicit solvation model, we extended our previous work on the hydrophobicity scale of amino acids. To this end, we employed two structural models, Model 1 and 2, differentiated solely by their C-terminal capping groups using an N- or O-methyl substituent, respectively. Results: Our findings revealed substantial similarities between the models, validating the lipophilicity values for the non-standard side chains. Differences were observed in fewer cases, indicating an effect of the capping group on the side chain hydrophobicity. This effect is expected as one model contains a hydrogen bond donor (Model 1) while the other one uses a hydrogen bond acceptor (Model 2). Conclusions: Overall, both models exhibit good correlations with the experimental values, with Model 1 showing lower statistical errors. In addition, our predictions were able to correctly predict the experimental hydrophobicity change due to the number of acetylated lysines in peptide pairs determined by HPLC, suggesting that our scale can be employed for proteomics studies that include post-translational modifications beyond acetylation.